Viral load in interferon treated & untreated patients of HCV - Alamzeb Jadoon; Ayesha Gohier (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Hepatitis C (HC) is a chronic viral disease that chronically infects liver cells. It has got at least 6 genotypes. The virus uses cellular machinery to multiply and increase in number. Viral load is the copies of HC virus ribonucleic acid (RNA) that can be quantitatively measured on polymerase chain reaction (PCR) test. There are many treatment options available for the treatment of HCV, including standard interferon, pegylated interferon with oral anti-viral drugs. In our research, we studied the levels of viral load in Hepatitis C (HC) positive patients who were treated with interferon and those HC-positive patients who were untreated and observe the effect of interferon treatment on viral load. To measure and compare the viral load in treated and untreated patients of the Hepatitis C virus. METHODOLOGY: After obtaining written consent, a total of 54 HC patients, both male and female, were included in our study that were further divided into two groups Group-I included 26 freshly diagnosed patients of HC and Group II of 28. All the patients were from the Hazara division in Khyber Pakhtunkhwa (KPK), Pakistan. Quantitative PCR was performed to assess the viral load. Data obtained were analyzed using IBM SPSS version 23 and was also compared within groups. RESULTS: There was a significant difference (p≤0.001) found in the viral load of interferon-treated and untreated patients of hepatitis C, but there was no significant difference found when compared among gender-different districts of the Hazara region. CONCLUSION: Significantly higher viral load in untreated patients of HCV when compared to interferon-treated patients of HCV suggest that interferon is still effective against HCV.